The lion storyteller bedtime book / world folk tales especially for reading aloud - Hartman, Bob.; Poole, Susie (Oxford, England ; Colorado Springs, CO : Lion Pub., 1998)
Contains forty bedtime stories, including tales and legends and stories from around the world.
4.4
3-6
Keywords: Folklore; Folklore